Analysis of Consumer Rights Protection Against the Misuse of Personal Data in Fintech Services - Bintang Mahacakri Lisan Putri; Rohaini; Pham Hong Nhung; Ria Wierma Putri (APPTHI, 2025)
The implementation of personal data protection regulations in the Indonesian fintech sector, specifically Law Number 27 of 2022 concerning Personal Data Protection and Financial Services Authority Regulation Number 77 of 2016, shows significant progress in implementing a comprehensive legal framework. This framework adopts international standards such as the General Data Protection Regulation, is supported by the establishment of a Personal Data Protection Agency, and mandates reporting of data breach incidents. However, covering personal data remains a serious threat, resulting in financial losses, psychological distress, and reputational damage for consumers. This highlights the challenges in consistent law enforcement, low digital literacy among the public, and the need for wider implementation of advanced security technologies. To improve legal protection, it is important to strengthen oversight and law enforcement mechanisms, improve digital literacy among the public through continuing education, mandate the implementation of advanced security technologies by fintech providers, and regulate reporting and complaint mechanisms.